Seasonal and interannual variability of nitrate in the eastern Chukchi Sea: Transport and winter replenishment. (July 2020) - Mordy, Calvin W.; Bell, Shaun; Cokelet, Edward D.; Ladd, Carol; Lebon, Geoff; Proctor, Peter; Stabeno, Phyllis; Strausz, David; Wisegarver, Eric; Wood, Kevin
Abstract: Rapid changes in sea ice and ocean properties are occurring in the Chukchi Sea, and there is considerable uncertainty how these changes might influence nutrient distributions and ultimately primary productivity. Although inorganic nitrogen is a limiting nutrient, there are few reports on seasonal or interannual variability of nitrate, especially those focused on wintertime replenishment of nitrate. This study examined six years of hourly measurements of nitrate at multiple mooring locations off Icy Cape between 2010 and 2018 with a focus on winter replenishment in relation to northward transport. Nitrate concentrations are lowest in newly formed winter water, and rates of local nitrate replenishment appear low relative to the nutrient flux through Bering Strait. There is considerable interannual variability in transport over the northeastern shelf of the Chukchi Sea that is driven by northerly (weakens transport) and southerly (strengthens transport) wind events. Anomalously low nitrate concentrations were observed in the winter of 2011–2012 when transport was negligible, and locally formed, low nitrate winter water remained on the shelf. During winters with the highest transport (2010–2011, 2017–2018), pre-bloom (15 May) nitrate concentrations were high and closely resembled nitrate concentrations in the Bering Sea from the previous fall. In recent years, there has been an increase in southerly wind events. As these conditions enhance total transport and nutrient flux through Bering Strait, contemporary Bering Sea water is advected onto the northern Chukchi Sea shelf. In the presence of southerly wind events, nutrient measurements in the northern Bering Sea in fall can be used to predict pre-bloom nitrate concentrations available for sustaining primary production in the eastern Chukchi Sea the following spring. Since 2005, inorganic nitrogen concentrations in the northern Bering Sea have varied between 11 and 22 μM; an indication that net community production over the eastern Chukchi Sea may have varied between 30 and 70 g C m −2 during this time.